0 голосов
42 оценили
от (58 баллов) 2 в категории Алгебра

Составьте многочлен p(x) = p1(x) + p2(x) – 4p3(x) и запишите его в стандартном виде, если: p1(x) = - 2x^2 + 3x; p2(x) = 4x^2 – 3; p3(x) = 2x – 4.

2 Ответы

0 голосов
от (82 баллов) 1
 
Лучший ответ

p(x) = p1(x) + p2(x) – 4p3(x) , если  p1(x) = - 2x^2 + 3x; p2(x) = 4x^2 – 3; p3(x)=2x–4,то

p1(x) = 3x + -2x^2

p2 (x) = 4x^2-3 

p3 (x) = 2x-4

p(x) = (4x^2-3) + (- 2x^2 + 3x) - 4(2x – 4)

p(x) =  2х^2 - 5х - 13 

Ответ: 2x^2-5x -13 =0

0 голосов
от Одаренный (1.8 тыс. баллов) 2 2 6

p(x) = p1(x) + p2(x) – 4p3(x)

p1(x) = - 2x^2 + 3x; p2(x) = 4x^2 – 3; p3(x) = 2x – 4.

р(х) = (- 2x^2 + 3x) + (4x^2 – 3) - 4(2x – 4)

р(х) = - 2x^2 + 3x + 4x^2 – 3 - 8х +16

р(х) = 2х^2 - 5х - 13

2х^2 - 5х - 13 = 0

...